The conceptual model of DFD-technology - Georgiy N. Kalyanov (Открытое образование (Москва), 2017)
The presence of large number of models and methods for structural modeling of business processes and systems has made urgent the development of standardized language for structural analysis and design, suitable for modeling as organizational management, and software systems (similar to UML for the object-oriented systems’ design).The paper proposes a draft of such a language based on data flow diagrams (DFD diagrams) as the most frequently used in functional structural modeling.As part of the work in this direction a conceptual model language is proposed, named DFD-technology, integrating structural models for different purposes based on DFD-diagrams, and reflecting functional, informational and behavioral aspects of the modeled object.The article also analyzes the syntax, semantic and pragmatic aspects of the introduced unified modeling language.For a formal description of the syntax, it is proposed to use the apparatus of the mixed grammars, a combination of graph and regular grammars. The article gives a grammar description to generate a simple dialect of DFD technology, informally described semantic aspects of language, particularly the semantics of relations between objects of the language.Thus, the paper proposed a solution of unification and standardization problem of structural modeling languages, based on the integrated DFD-technology. The conceptual model of the technology is prepared, the syntax of the standardized language, using the technique of the mixed grammar and the semantic aspects of the language are described in detail.It should be noted that the proposed methods in the article and models occupy the central place in modern business processes theory.